Pengembangan Perangkat Pembelajaran Model Direct Instruction Berbasis Komputer dan Foto Handout Pokok Bahasan Keliling dan Luas Bangun Datar untuk Sekolah Dasar - Anisa Sholikah; I Nyoman Arcana (Universitas Sarjanawiyata Tamansiswa, 2017)
Abstract: This research and development aims to (1) Develop appropriate learning toolkit model direct instruction in area and perimeter section for primary school. (2) To determine the feasibility of appropriate learning toolkit which developed. The development method used in this study followed the procedures suggested by Borg and Gall which consist of five steps, namely (1) exploration study, (2) develop preliminary form of product, (3) expert validation and product revision, (4) limited field testing and product revision, and (5) main field testing and the final product. The learning toolkit had been validated by experts and has been tested twice: the limited field testing against 5 students and the main field testing against the 20 students at SDN Kranggan. Results of the research is the learning toolkit entitled The Learning Toolkit Model Direct Instructin Based Computer and Handout Photoâ€™s in Area and Perimeter Section for Primary School. The learning toolkit consists of a syllabus, lesson plans, student worksheets, instructional media, and an assesment. Based on the validation results, the learning toolkit was proper to use. The average score are average score of lesson plans 3.37 (good), average score of student worksheetsÂ 3.28 (good), average score instructional media from material expert 3.22 (good), average score instructional media from media expert 3.94 (very good), average score of assesment 3.33 (good), and average score questionnaire responses of students is 35.56 (very good). This result is also supported by the average achievement test scores of students was 83 with the number of students who achieve minimum mastery criteria is 90%. This test score had exceeded the minimum mastery criteria which definited by the school, the minimum mastery criteria is 75.